The effect of corporate governance and human capital on integrated reporting of top 100 Malaysian public listed companies: the moderating role of board gender diversity / Nur Zharifah Che Adenan - Che Adenan, Nur Zharifah (2022)
Integrated reporting is a tool that assists stakeholders in understanding how a company performs and making more sustainable decisions. The purpose of this study is to investigate the Integrated Reporting’s existence of public listed companies and examine the relationship amongst corporate governance mechanisms (board size, board independence, managerial ownership, audit committee, and CEO Duality), human capital (Muslim directors, postgraduate directors, boards with accounting and law background, and director's age), and integrated reporting in the top 100 Malaysian public listed companies for the years ended 2018, 2019, and 2020, as well as board gender diversity as a moderator. The annual reports of the top 100 corporations listed on Bursa Malaysia's main board for 2018, 2019, and 2020 were examined using content analysis to determine the firm's integrated reporting. STATA 16 was used to perform descriptive statistics, correlation, and multiple regression analysis using the Ordinary Least Squares (OLS) method. The study results revealed that board size, managerial ownership, audit committee, CEO duality, Muslim directors, and directors with a law background significantly influence the existence of integrated reporting of public listed companies in Malaysia. The most significant variable that influences the existence of integrated reporting is the audit committee. The moderating effect of the board's gender diversity on the association between corporate governance mechanisms, human capital, and integrated reporting showed that the board gender diversity moderates the relationship between the audit committee, Muslim directors, board age, and integrated reporting. The significance of the study is to highlight the increasing awareness of recent research and the company's attention to the benefits of IR among publicly listed companies worldwide and specifically in Malaysia. In line with the International Integrated Reporting Council's current recommendation; thus, this study may contribute to a better understanding of the need to provide transparent information on the company's actual performance and assist stakeholders in making some assessments about the company's operations.